1967
DOI: 10.3950/jibiinkoka.70.963
|View full text |Cite
|
Sign up to set email alerts
|

An Electromyographic Study of Recurrent Laryngeal Nerve Paralysis

Abstract: Electromyographic investigations of the intrinsic laryngeal muscles were carried out in 29 human cases with recurrent laryngeal nerve paralysis and in 14 canine cases, in which unilateral recurrent laryngeal nerve paralysis was experimentally caused by various methods of crushing, section and suture after section of the nerve. The observations in dogs were repeated before the operation and several minutes, several days, a i onth and every months up to death after causing paralysis. The laryngoscopic view of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“… 14 In related reports, the recovery of imperceptible adductive vocal fold movement was low, ranging from 0% to 29%. 15–18 In our study, vocal fold movement recovered in seven of eight (87.5%) animals in the bFGF group and three of eight (37.5%) animals in the PBS group after 90 days. Furthermore, we observed both adduction and abduction of the vocal fold in some animals treated with bFGF.…”
Section: Discussionsupporting
confidence: 49%
“… 14 In related reports, the recovery of imperceptible adductive vocal fold movement was low, ranging from 0% to 29%. 15–18 In our study, vocal fold movement recovered in seven of eight (87.5%) animals in the bFGF group and three of eight (37.5%) animals in the PBS group after 90 days. Furthermore, we observed both adduction and abduction of the vocal fold in some animals treated with bFGF.…”
Section: Discussionsupporting
confidence: 49%
“…Several case reports since then reported improved vocal fold mobility after reinnervation, 2–4 but most investigators have not observed restored mobility. 5–9 Some have shown return of electromyographic (EMG) activity to the reinnervated larynx, but without functional movement. 10–14 …”
Section: Introductionmentioning
confidence: 99%
“…l'innervation est complexe -en l'oc currence l'existence de muscles adducteurs et abducteurs du pli vocal innervés par un même récurrent -il peut se produire des «erreurs d'aiguillage»: en effet, des axones régénérés à fonction abductricc peuvent s'engager dans des faisceaux menant à des muscles adduc teurs et réciproquement. Ce phénomène d'in nervation paradoxale [4,[8][9][10][11][12][13] peut donner lieu à des syncinésies d'abducteurs et d'ad ducteurs, ce qui est néfaste sur le plan fonc tionnel.…”
Section: La Réduction Unilatérale De Mobilité D'un Pli Vocalunclassified